2001
DOI: 10.1007/bf02897306
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induces DNA damage via reactive oxygen species in human cells

Abstract: To elucidate arsenic-induced oxidative DNA damage, the genotoxicity of arsenic in human cells was comparatively studied with single cell gel electrophoresis (SCGE) assay in combination with the observation of the protective effects of dimethyl sulfoxide (DMSO) and catalase. Arsenic, at the concentration of 2.4 mM by coincubation for 24 hours, significantly induced DNA damage in HL60, a human promyelocytic leukemia cell line. In contrast, significant DNA damage was found in human mononucleocytes at the concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Other recent studies have suggested that arsenite activates NADH oxidase to produce O 2 -, which then causes oxidative DNA damage (13,24). These studies suggest that arsenic may trigger oxidative stress through multiple pathways, but H 2 O 2 and O 2 -are the main ROS involved in arsenicinduced DNA damage, as shown in our previous study (5).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other recent studies have suggested that arsenite activates NADH oxidase to produce O 2 -, which then causes oxidative DNA damage (13,24). These studies suggest that arsenic may trigger oxidative stress through multiple pathways, but H 2 O 2 and O 2 -are the main ROS involved in arsenicinduced DNA damage, as shown in our previous study (5).…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies showed similar results using reactive oxygen species (ROS) scavengers such as SOD, CAT, and dimethyl sulfoxide (DMSO) to counteract mutagenicity, DNA fragmentation, and micronuclei (MN) caused by As (2)(3)(4). We observed that DMSO and CAT basically abolished most of the As-induced DNA single strand breaks (SSBs) in human cells with single-cell gel electrophoresis (SCGE) assay (5). These observations have provided indirect but powerful evidence indicating that hydrogen peroxide (H 2 O 2 ) and superoxide anion (O 2 -) are chiefly involved in the genotoxicity of As.…”
mentioning
confidence: 78%
“…The antioxidant potential of DMSA has earlier been reported against arsenic (Flora, 1999) and lead (Gurer et al, 1998). Arsenic is known to induce DNA damage through mediation of reactive oxygen species (ROS) (Li et al, 2001). It is also reported that arsenic may trigger oxidative stress through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…As cadmium inhibits the mismatch repair (MMR) [42,43], the cellular error gets amplified and mutations in genes become more, thereby it leads to the most dreadful cancer [29]. Cadmium can also inhibit enzymes such as superoxide dismutase (SOD) [44], catalase [45,46], glutathione peroxidase [44], glutathione reductase [45] and glutathione-S-transferase [33] and this inhibition leads to the formation of free OH radicals [47].…”
Section: Through Enzyme Inhibitionmentioning
confidence: 99%
“…The toxicity mechanism of heavy metal ions is through enzyme inhibition, oxidative stress and impaired antioxidant metabolism. These mechanisms show adverse health effects through free radical generation that leads to DNA damage [28][29][30], lipid peroxidation and depletion of protein sulfhydryl [12,21]. This review highlights the few toxicity mechanisms of heavy metal ions that inhibit the enzymes and induce oxidative stress thereby affecting human health.…”
Section: Introductionmentioning
confidence: 97%